The dynamics of open innovation in the innovation ecosystems' lifecycle - Spindler, Everson dos Santos (2023)
Organizations leverage innovation to stay competitive amidst rising competition and fast technological changes. Innovation now extends beyond organizational borders through collaborations, sparking discussions among academia, governments, and entrepreneurs. The concept of open innovation, introduced by Chesbrough (2003), is a prominent theoretical framework exploring these multi-actor collaborations, but has frequently been used at the level of the firm, lacking further exploration in other level of analysis to unravel contingencies and the dynamics of open innovation. This dissertation aims to analyze how open innovation influences the emergence, development, and performance of regional innovation ecosystems. We have identified three main theoretical gaps that relates open innovation and regional innovation ecosystems. The first gap is related to how open innovation and innovation ecosystems approaches are interconnected using a life cycle perspective to comprehend the different stages of the ecosystem. The second gap refers to the mechanisms of open innovation employed in regional innovation ecosystems. Lastly, the third gap addressed in this dissertation explores open innovation in the context of emerging economies, which has been under investigated in the open innovation approach since its conception. Three studies were developed to fill such gaps. The first paper is a theoretical essay that analyzes the role and the mechanisms of open innovation throughout the life cycle of innovation ecosystems. We propose an integration between open innovation and innovation ecosystems and presented a set of components to assess open innovation at different stages of the innovation ecosystem's life cycle. The second paper adopts a qualitative case study in the Serra Gaúcha and aims to evaluate the role of open innovation mechanisms within the regional innovation ecosystem. The paper highlights the importance of open innovation in the development of regional innovation ecosystems. We found that open innovation mechanisms are crucial in the early stages of an innovation ecosystem, facilitating the creation of a network identity and alignment of strategic objectives and contributing for a change in the level of openness among the actors participating in the ecosystem over time. The third paper presents a quantitative study conducted within the regional innovation ecosystem of Rio Grande do Sul. Our results revealed that openness exerts a positive and significant impact on ecosystem performance. This suggests that promoting collaboration and utilizing knowledge exchange within the ecosystem contribute to enhancing firms' level of openness. Our findings also indicate a favorable correlation between openness and the abilities to acquire and exploit. Finally, the research underscores the importance of fostering a culture of openness and collaboration within regional innovation ecosystems. By adopting open innovation mechanisms and promoting knowledge exchange, strategic alignment, and increased engagement among ecosystem actors, open innovation can serve as a catalyst for driving innovation, economic growth, and prosperity within the region.